2015
DOI: 10.1038/jes.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traffic-related air pollution on acute changes in cardiac autonomic modulation during rest and physical activity: a cross-over study

Abstract: People are often exposed to traffic-related air pollution (TRAP) during physical activity but it is not clear if physical activity modifies the impact of TRAP on cardiac autonomic modulation. We conducted a panel study among 28 healthy adults in Barcelona, Spain to examine how physical activity may modify the impact of TRAP on cardiac autonomic regulation. Participants completed four two-hour exposure scenarios that included either rest or intermittent exercise in high and low-traffic environments. Time-and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
(19 reference statements)
2
22
0
1
Order By: Relevance
“…The decrease of both, average SDNN and PNN50 can be interpreted as a reduced autonomic activity (Ewing et al, 1984;Electrophysiology Taskforce Guidelines, 1996;Mietus et al, 2002). This type of acute response was reported by other groups before (Devlin et al, 2003;Pope et al, 2003;Wu et al, 2010;Huang et al, 2014;Nyhan et al, 2014;Wagner et al, 2014;Weichenthal et al, 2014;Cole-Hunter et al, 2015;Hemmingsen et al, 2015;Mordukhovich et al, 2015;Lee et al, 2016). Interestingly, SDNN at high exposure levels is just slightly below the average SDNN, while PNN50 drops to near zero, which is suggestive of mostly parasympathetic withdrawal.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The decrease of both, average SDNN and PNN50 can be interpreted as a reduced autonomic activity (Ewing et al, 1984;Electrophysiology Taskforce Guidelines, 1996;Mietus et al, 2002). This type of acute response was reported by other groups before (Devlin et al, 2003;Pope et al, 2003;Wu et al, 2010;Huang et al, 2014;Nyhan et al, 2014;Wagner et al, 2014;Weichenthal et al, 2014;Cole-Hunter et al, 2015;Hemmingsen et al, 2015;Mordukhovich et al, 2015;Lee et al, 2016). Interestingly, SDNN at high exposure levels is just slightly below the average SDNN, while PNN50 drops to near zero, which is suggestive of mostly parasympathetic withdrawal.…”
Section: Discussionsupporting
confidence: 64%
“…In line with these ill-health effects of PM was the observation that PM 2.5 exposure is associated with reduced HRV: in controlled exposure of rats to PM 2.5 , HRV was reduced during ongoing exposure (Wagner et al, 2014). In a series of epidemiological (Pope et al, 2003;Wu et al, 2010;Huang et al, 2014;Nyhan et al, 2014;Mordukhovich et al, 2015;Lee et al, 2016) as well as controlled PM-exposure (Devlin et al, 2003;Weichenthal et al, 2014;Cole-Hunter et al, 2015;Hemmingsen et al, 2015) studies, small reductions in HRV within an hour after PM exposure were observed. However, a recent meta-analysis of panel studies investigating HRV effects of PM 2.5 (Buteau and Goldberg, 2016) questioned the association between PM 2.5 and frequently used indices of HRV.…”
Section: Introductionmentioning
confidence: 78%
“…Traffic-related air and noise pollution exposure is recognized as one of the major public health challenges of the 21st century. It is well-known that exposure to air and noise pollution contributes to detrimental effects on respiratory and cardiovascular systems [1][2][3]. These exposures are indeed a major contributor to increased length of in-hospital stay, morbidity, and mortality associated with chronic diseases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…While a person is physically active, breathing and ventilation rates increase, and thus the amount of air pollutant inhaled is likely to increase [1]. Even with the expected health benefits of bicycling, poor air quality may generate health trade-offs, such as acute decrements in respiratory function [2][3][4], decreased heart rate variability [5,6], decreased microvascular function [7], and increased risk of myocardial infarction [8]. It has also become widely believed that exposure to traffic-related air pollutants, such as particulate matter with an aerodynamic diameter below 2.5 µm (PM 2.5 ), can cause respiratory and chronic diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%